2020
DOI: 10.3390/molecules25020273
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Chromium(II) Complexes with Chelating Bis(alkoxide) Ligand and Their Reactions with Organoazides and Diazoalkanes

Abstract: Synthesis of new chromium(II) complexes with chelating bis(alkoxide) ligand [OO]Ph (H2[OO]Ph = [1,1′:4′,1′’-terphenyl]-2,2′’-diylbis(diphenylmethanol)) and their subsequent reactivity in the context of catalytic production of carbodiimides from azides and isocyanides are described. Two different Cr(II) complexes are obtained, as a function of the crystallization solvent: mononuclear Cr[OO]Ph(THF)2 (in toluene/THF, THF = tetrahydrofuran) and dinuclear Cr2([OO]Ph)2 (in CH2Cl2/THF). The electronic structure and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Two bulky alkoxide donors in H 2 [OO] Ph were linked together with a terphenyl linker. 76,77 The resulting Fe(II) complex Fe[OO] Ph (THF) 2 (Fig. 16) replicated key structural features of the complexes with monodentate alkoxides Fe (OR) 2 (THF) 2 and Fe(OR′) 2 (THF) 2 , featuring overall seesaw geometry.…”
Section: Dalton Transactionsmentioning
confidence: 70%
“…Two bulky alkoxide donors in H 2 [OO] Ph were linked together with a terphenyl linker. 76,77 The resulting Fe(II) complex Fe[OO] Ph (THF) 2 (Fig. 16) replicated key structural features of the complexes with monodentate alkoxides Fe (OR) 2 (THF) 2 and Fe(OR′) 2 (THF) 2 , featuring overall seesaw geometry.…”
Section: Dalton Transactionsmentioning
confidence: 70%
“…They investigated its reactivity in catalyzing nitrene transfer to isocyanide 4b within a bis(alkoxide) ligand environment (as illustrated in Scheme 4 ). 35 Their research team explored the use of less bulky aryl azides, which, however, did not lead to the formation of carbodiimides due to the absence of Cr(IV) imido, a crucial intermediate. Their research deduced that carbodiimide synthesis via nitrene transfer is feasible only in the presence of bulky aryl azides or aryl isocyanides.…”
Section: Early Reports On the Catalytic Reaction For The Nitrene-to-i...mentioning
confidence: 99%
“…80 In 2020 the same research group reported the use of dichromium complex 167 with chelating bis(alkoxide) ligands in the context of catalytic synthesis of carbodiimides (165) from azides (130) and isocyanides (5) (Scheme 43). 81 The authors observed that only sterically encumbered azides were able to participate in the nitrene transfer reaction. Based on their previous work (Scheme 42) the authors postulate that non-bulky azides form a saturated catalytically inactive Cr IVbis(imido) complex.…”
Section: Nitrene Transfer To Isocyanidesmentioning
confidence: 99%